Factor synergy analysis and merger strategy models in investigation of telecommunication operators' performance - Malyeyeva, Olga; Kosenko, Viktor; Davydovskyi, Yurii; Boiev, Dmitriy (Національний технічний університет "Харківський політехнічний інститут", 2020)
The subject of the study is the process of choosing a strategy to improve the effectiveness of telecom operators, given the trend of growth in multitraffic in data networks. The purpose of the work is to analyze the synergy of factors and develop models of traffic of data networks in the implementation of the strategy of merger of telecommunication operators. The following tasks are solved in the article: analysis of telecommunication development strategies; building a network model of synergistic effect in the implementation of development strategies; development of a model of data flow intensity in the integrated networks. The following research methods are used: statistical and system analysis, cause and effect models, mathematical programming models, and vector matrix models. The following resultsare obtained: The tendencies of development of multiservice services in the sphere of infocommunications are considered. Here are some basic strategies for developing a communications company. It is shown that merger and acquisition strategies are nowadays a means of integrating the necessary resources, contributing to competitive advantage. A mathematical model of linear programming is used to make the decision to invest in development strategies. The task of evaluating the effectiveness of development towards expanding the number of service users is considered. A network model in the form of a cause and effect diagram to investigate the mutual influence of sales factorswas formed. The economic manifestation of the synergistic effect of companies in the implementation of the merger strategy is considered. A multilevel data flow model is used to study the intensities of data flows in a unified network. Conclusions: Due to the increasing volume and heterogeneity of infocommunication network traffic, telecom operators are using merger strategies to pool network management resources. Thus there is a synergistic effect of factors affecting sales of services. The changes in traffic and performance of the consolidated network structure are investigated on the basis of a three-tier hierarchical model. The direction of further research is to simulate network load with different technical structure characteristics to evaluate the effectiveness of a reengineering strategy.

Предметом дослідження в статті є процеси вибору стратегії для підвищення ефективності діяльності операторів зв’язку з огляду на тенденції зростання мультитрафіку в мережах передачі даних. Мета роботи – аналіз синергії факторів і розробка моделей трафіку мереж передачі даних при реалізації стратегії злиття операторів зв’язку. В статті вирішуються наступні завдання: аналіз стратегій розвитку операторів зв’язку; побудова мережної моделі синергетичного ефекту при реалізації стратегій розвитку; розробка моделі інтенсивності потоків даних в об’єднаних мережах. Використовуються такі методи дослідження: статистичного та системного аналізу, причинно-наслідкові моделі, моделі математичного програмування та векторно-матричні моделі. Отримано наступні результати: Розглянуто тенденції розвитку мультисервісних послуг у сфері інфокомунікацій. Наведено основні стратегії розвитку компаній з надання послуг зв’язку. Показано, що стратегії злиття та поглинання сьогодні виступають засобом інтеграції необхідних ресурсів, що сприяє досягненню конкурентних переваг. Для прийняття рішення з інвестування у стратегії розвитку застосовується математична модель лінійного програмування. Розглянуто завдання оцінювання ефективності розвитку в напрямку розширення кількості споживачів послуг. Сформована мережна модель у вигляді причинно-наслідкової діаграми для дослідження взаємовпливу факторів обсягу продажів. Розглянуто економічний прояв синергетичного ефекту компаній при реалізації стратегії злиття. Для дослідження інтенсивностей потоків даних в об’єднаній мережі використовується модель потоків даних багаторівневої структури. Висновки: Внаслідок зростаючих обсягів та неоднорідності трафіку інфокомунікаційних мереж операторами зв’язку застосовуються стратегії злиття для об’єднання ресурсів управління мережею. При цьому виникає синергетичний ефект факторів, що впливають на обсяги продажів послуг. Дослідження змін трафіку та ефективності структури об’єднаної мережі проводиться на основі трирівневої ієрархічної моделі. Напрямком подальших досліджень є моделювання навантаження мережі з різними характеристиками технічної структури для оцінки ефективності стратегії реінжинирінгу.
Аналіз синергії факторів та моделі стратегії злиття в дослідженні ефективності діяльності операторів зв’язку
Keywords: data networks; development strategies; influence of factors; traffic intensity; мережі передачі даних; стратегії розвитку; вплив факторів; інтенсивність трафіку